Occurrence of pediatric inflammatory conditions in COVID-19: an integrative review (Research, Society and Development, 2021)
Objective: to integrate, compile and discuss the clinical-epidemiological data of pediatric patients who were exposed to the SARS-CoV-2 virus and developed multisystemic inflammatory syndromes. Methodology: The research was carried out in September 2020, from the electronic databases of the Biblioteca Virtual em Saúde (BVS), Medical Literature Analysis and Retrieval System Online (MEDLINE), SCOPUS, Scientific Electronic Library Online (SciELO) and Google Scholar. The descriptors were organized in the following proposal: ((““ COVID-19 ”OR“ SARS-CoV-2 ”OR“ Coronavirus ”AND“ Kawasaki Disease ”AND“ Children ”OR“ Adolescent ”OR“ Pediatric ”) OR (“ COVID- 19 ”OR“ SARS-CoV-2 ”OR“ Coronavirus ”AND“ Multisystem Inflammatory Syndrome in Children ”OR“ Pediatric Multisystem Inflammatory Syndrome ”AND“ Children ”OR“ Adolescent ”OR“ Pediatric ”)). The searches were delimited by the inclusion criteria: language (English, Portuguese and Spanish), indexing in the databases and full text. The exclusion criteria were: inadequate studies, duplicate samples and incompatible with the purpose of this review. Results: 1,324 articles were identified, of which only 38 were included in the review. The majority of patients were male (59%), African-American (35%) with an average age of 8.8 years. Pediatric multisystem inflammatory syndrome was diagnosed in 67% of patients who presented mainly fever (94%), gastrointestinal symptoms (65%) and possible cardiac complications (32%), hypotension (27%) and shock (17%). Conclusion: The information points to a post-viral syndrome that appears between two and four weeks after contamination by Sars-CoV-2, the impacts caused are still unknown, therefore, health service teams must be attentive to deal with this new aspect of COVID-19.